Understanding Complex Systems Through Mental Models and Shared Experiences: A Case Study. (October 2015) - Bekebrede, Geertje; Lo, Julia; Lukosch, Heide
Background. Our world today is made up ofcomplex, socio-technical systems like large infrastructure systems, global logistic chains and information networks.Simulation games represent one way to enableparticipation andgovernance of such systems. Aim. The current study explores the development of mental models and shared experiences of professionals and students through a simulation game. Method. Thesimulation game SIMPORT-MV2 focused on the development of a new port area in the Port of Rotterdam, The Netherlands. Insights in the perceiveddevelopment of mental models were measured through questionnaires and through observations in the debriefing. Likewise, observations in the debriefing were obtained for measurements ofshared experiences . Results. Results showed that participants perceivedpositive learning on their declarative, procedural and strategic knowledge (mental model) about the port project. A significant difference was found for both the overallperceived knowledge and thestrategic knowledge between students and professionals. Furthermore, qualitative findings showed that players are enabled to probe designs of, to gain insights into, and to develop an understanding ofcomplex systems in a safe environment throughshared experiences . Conclusions. This study shows that it is possible to design asimulation game that represents such acomplex socio-technical system based on alayered approach of agent, network and system behavior.